Organic farming and happiness: A path analysis - Ghislain B. D. Aïhounton; Arne Henningsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2024)
While price premiums incentivise farmers to engage in organic farming, these premiums are frequently insufficient to compensate for lower yields, resulting in no monetary benefits from adopting organic farming. This study goes beyond purely monetary outcomes and investigates how organic farming is related to both monetary and non-monetary outcomes, including farmers' general life satisfaction or 'happiness'. We use data collected from organic and conventional cotton growing households in Benin and employ Structural Equation Modelling in order to investigate the pathways through which organic farming is related to happiness. Our findings indicate that organic farming is positively associated with happiness through farmers' improved (self-reported) health and increased satisfaction with their work as well as through a direct relationship between organic farming and happiness. While a negative association between organic farming and income exists, it only reduces the overall positive relationship between organic farming and happiness to a very limited extent. Thus, our results show that non-monetary outcomes may be important drivers of the adoption of sustainability standards as well as relevant measures of farmers' welfare when evaluating policies and programmes.
Keywords: D60; I31; O13; Q12; Q18; 330; Organic farming; happiness; life satisfaction; non-monetary measures of wellbeing; income; farm households